An Examination Of Herding Behavior On Stock Market: An Halal Perspective - Dewi Suryani Sentosa (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
The objective of this study is examining herding on stock market in an halal perspectivefor understanding as the way of thought and it could result the right decision for investor. The decision can be obtained from herding which is seen as a factor of  stock market more volatile and risky. This behavior is done by the investor due to feel doubt in choosing stock, because there are no other choices to make some decisions and they assume that other investors have some informations. On the other hand, herding can affect the level of risk to be faced. The problem being analyzed are; First, how the halal perspective about herding behavior. Second, what are the criteria of herding base on halal perspective. This study was writed over a month period beginning in August, 2018. The primary data is mainly gathered from Al-Qur’an, al Hadits, and ushul Fiqh. To support the data, an in-depth analyze technique was also used. In addition, the secondary data from journal’s articles, books, and other related literatures were also utilized. This paper is using descriptive method of analyses, and include in the literature research category. The findings show that herding in halal perspective is allowed but it must be in accordance with the knowledge of stock analyzing and who person they follow. It could not followed blindly to result decision. This study would make Halal Science Research having a potential to answer the shortcoming found in phenomenon of stock market.